Revolutionizing Foam Cutting Efficiency in Indonesia with AutoCAD: Merevolusi Efisiensi Pemotongan Busa di Indonesia dengan AutoCAD - Hakim, Resha Hibatur Rahman; Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
Foam set machines are essential for cutting foam sheets in various industries, including furniture, textiles, and foam manufacturing. PT. Amangriya, using a custom foam set machine for two years, identified the need for efficiency improvements. This research aimed to enhance the foam set machine's design using AutoCAD software. Key improvements included an automatic top clamp, a flexible side clamp, and reduced machine dimensions. These modifications resulted in a more efficient and compact machine, facilitating easier manufacturing and assembly processes. The study highlights the potential for significant efficiency gains in the foam manufacturing industry through design enhancements. Highlight: Enhanced machine design with AutoCAD software improves efficiency and functionality. Key modifications include automatic top clamp and flexible side clamp. Reduced machine dimensions facilitate easier manufacturing and assembly. Keywoard: Foam set machine, design enhancement, efficiency, AutoCAD, manufacturing